Orthostatic Hypertension: The Contribution of Cardiovascular Risk Factors and Body Composition - Solis, Sara Estefania (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2025)
Orthostatic hypertension is an emerging clinical entity characterised by an exaggerated increase in blood pressure upon standing. Although its recognition has grown in recent years, the historical heterogeneity in diagnostic definitions and methodologies has complicated comparisons across studies and delayed standardised clinical understanding. In response to these challenges, a recent consensus definition has been proposed, providing a unified framework for research and clinical practice. This thesis aims to investigate the prevalence and clinical associations of exaggerated orthostatic pressor response (EOPR) and orthostatic hypertension (OHT), as defined by the recent consensus criteria, in older adults. Furthermore, it explores the contribution of body composition parameters, to these blood pressure phenotypes. Given the physiological influence of body composition parameters understanding their potential role offers novel insights into the potential underlying mechanisms of OHT. Using data from two independent cohortsthe Technology Research for Independent Living (TRIL) Clinic and the FRAILMatics Clinical Studythis research determined the prevalence of EOPR and OHT, examined their associations with cardiovascular conditions and metabolic markers, and explored the relationships between body composition and orthostatic blood pressure changes. Orthostatic BP responses were assessed at multiple time stamps (including 60-, 90-, 120- and 180-seconds post-stand), allowing for a more nuanced characterisation of haemodynamic patterns. The prevalence of EOPR ranged from 7.0% to 24.3%, while that of OHT ranged from 7.0% to 21.5% across both cohorts. Notably, EOPR and OHT were significantly associated with female sex (p = 0.031, OR = 3.36, 95% CI: 1.1-10.0), heart failure (p = 0.019, OR = 2.5, 95% CI: 1.1-5.4), higher haemoglobin levels (p = 0.050, OR = 1.4, 95% CI: 1.0-2.0), and lower serum albumin, which appeared to have a protective effect (p = 0.041, OR = 0.85, 95% CI: 0.7-0.9). Variations in body composition also emerged as relevant factors, with associations observed for body mass index (BMI) (p = 0.033, OR = 1.0, 95% CI: 1.0-1.1), greater adiposity (p = 0.026, OR = 1.1, 95% CI: 1.0-1.3), and reduced muscle mass (p = 0.036, OR = 0.8, 95% CI: 0.7-0.9). These findings suggest that alterations in body composition may contribute to the pathophysiological mechanisms linking orthostatic blood pressure responses to increased cardiometabolic risk in older adults. By applying recent consensus definitions and evaluating body composition in this context, this study advances current understanding of OHT and its clinical significance, underscoring the need for further research to confirm causal pathways and develop targeted intervention strategies.
APPROVED
Keywords: orthostasis; aging; old adult; body composition; fat mass; muscle mass; ageing; orthostatic hypertension